2023
DOI: 10.3390/genes14020249
|View full text |Cite
|
Sign up to set email alerts
|

Framework of the Alu Subfamily Evolution in the Platyrrhine Three-Family Clade of Cebidae, Callithrichidae, and Aotidae

Abstract: The history of Alu retroposons has been choreographed by the systematic accumulation of inherited diagnostic nucleotide substitutions to form discrete subfamilies, each having a distinct nucleotide consensus sequence. The oldest subfamily, AluJ, gave rise to AluS after the split between Strepsirrhini and what would become Catarrhini and Platyrrhini. The AluS lineage gave rise to AluY in catarrhines and to AluTa in platyrrhines. Platyrrhine Alu subfamilies Ta7, Ta10, and Ta15 were assigned names based on a stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…Platy-1 elements mobilize via TPRT and therefore compete for the same LINE (L1) enzymatic machinery that Alu elements do to achieve successful propagation. Alu content has not yet been characterized in tamarins specifically, to determine if Alu amplification rates are lower due to the vast expansion of Platy-1 elements, as compared to other reported platyrrhine genomes [22][23][24][25][26]. However, we have observed that Platy-1 elements in tamarins and other genomes [5] are often flanked by one or more Alu elements.…”
Section: Discussionmentioning
confidence: 58%
“…Platy-1 elements mobilize via TPRT and therefore compete for the same LINE (L1) enzymatic machinery that Alu elements do to achieve successful propagation. Alu content has not yet been characterized in tamarins specifically, to determine if Alu amplification rates are lower due to the vast expansion of Platy-1 elements, as compared to other reported platyrrhine genomes [22][23][24][25][26]. However, we have observed that Platy-1 elements in tamarins and other genomes [5] are often flanked by one or more Alu elements.…”
Section: Discussionmentioning
confidence: 58%